2006
DOI: 10.1002/humu.9411
|View full text |Cite
|
Sign up to set email alerts
|

Study of four genes belonging to the folate pathway: transcobalamin 2 is involved in the onset of non-syndromic cleft lip with or without cleft palate

Abstract: Cleft lip with or without cleft palate (CL/P) is the most common inborn craniofacial anomaly. Affected individuals require extensive medical and psychosocial support. Although CL/P has a complex and poorly understood etiology, increasing evidence of folate pathway involvement has been collected. So far, only the MTHFR gene has been extensively investigated as a risk factor for CL/P, while little has been done to test genetic variations in the folate biosynthetic pathways that may influence the infant's suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 20 publications
3
50
3
4
Order By: Relevance
“…Peri-implantitis can happen with high frequencies in bone regeneration (60-63) also after cancer resection (64)(65)(66)(67)(68). In some pediatric conditions can be useful to have a low bacterial loading (69)(70)(71)(72)(73)(74)(75)(76)(77). During the prosthetic rehabilitation, bacterial dissemination is unavoidable, and when the IAJ is located at the level of the bone crest, the formation of biofilms in this area causes bone resorption, observed in the early stages of prosthetic load.…”
Section: Discussionmentioning
confidence: 99%
“…Peri-implantitis can happen with high frequencies in bone regeneration (60-63) also after cancer resection (64)(65)(66)(67)(68). In some pediatric conditions can be useful to have a low bacterial loading (69)(70)(71)(72)(73)(74)(75)(76)(77). During the prosthetic rehabilitation, bacterial dissemination is unavoidable, and when the IAJ is located at the level of the bone crest, the formation of biofilms in this area causes bone resorption, observed in the early stages of prosthetic load.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in interferon regulatory factor 6 (IRF6) can lead to Van der Woude syndrome, a dominant disorder that has CL±P as a common feature. Recently, it has been proposed and confirmed a strong association between genetic polymorphisms at the IRF6 locus, on 1p32.2 and CL±P, particularly in Asian and South American populations (26,(28)(29)(30)(31). Moreover, MYH9, a gene encoding for the heavy chain of non-muscle myosin IIA, is also considered a potential candidate in the CL±P onset.…”
Section: Human Genetic Factorsmentioning
confidence: 93%
“…The results of these study highlight that polymorphic variants at the MTHFR gene are responsible for a higher risk of having L±PC affected children. Folate receptors (FOLRs) mediate the delivery of 5-methyltetrahydrofolate to the interior of cells or between cells in a process known as potocytosis (20,28,29). In order to verify whether FOLRs could be involved in the onset of non-syndromic CL±P, a sample study consisted of patients and their mothers from 71 CL±P families and 75 sporadic cases was tested using linkage and linkage disequilibrium analyses.…”
Section: Supplements and Vitamins During Pregnancymentioning
confidence: 99%
“…It was not found an association between TCN2 (776C>G) and NSCL/P. Martinelli et al (11) investigated the association between NSCL/P and TCN2 (776C>G) gene in a case-parent triad and they suggested that this polymorphism might be functionally related with NSCL/P. On the other hand, later studies tried to replicate their findings, but could not confirm this association (10).…”
Section: Tcn2 and Mtrr Polymorphisms Study In Oral Cleftmentioning
confidence: 97%